2010
DOI: 10.1093/jhered/esq110
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic History of White Spruce During the Last Glacial Maximum: Uncovering Cryptic Refugia

Abstract: Although a recent study of white spruce using chloroplast DNA uncovered the presence of a glacial refuge in Alaska, chloroplast failed to provide information on the number or specific localities of refugia. Recent studies have demonstrated the utility of nuclear microsatellites to refine insights into postglacial histories. The greater relative rate of mutation may allow finer scale resolution of historic dynamics, including the number, location, and sizes of refugia. Genetic data were acquired from screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 33 publications
3
17
0
Order By: Relevance
“…More favorable environmental conditions for sexual reproduction and successful trembling aspen seedling establishment in this area [57, 58] may have contributed to increase allelic richness through recombination in populations from the Albertan foothills of the Rocky Mountains. The existence of a refugium in Beringia during the LGM has been reported for P. glauca [9, 23] and was consistent with the model simulation of suitable refugial habitats for this species (performed with the Community Climate Model and the Geophysical Fluid Dynamics Laboratory Model) [8], which suggested the presence of P. glauca in Beringia during the LMG. Moreover, those simulations also suggested the presence of suitable habitats for P. contorta and P. tremuloides in Beringia [8].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…More favorable environmental conditions for sexual reproduction and successful trembling aspen seedling establishment in this area [57, 58] may have contributed to increase allelic richness through recombination in populations from the Albertan foothills of the Rocky Mountains. The existence of a refugium in Beringia during the LGM has been reported for P. glauca [9, 23] and was consistent with the model simulation of suitable refugial habitats for this species (performed with the Community Climate Model and the Geophysical Fluid Dynamics Laboratory Model) [8], which suggested the presence of P. glauca in Beringia during the LMG. Moreover, those simulations also suggested the presence of suitable habitats for P. contorta and P. tremuloides in Beringia [8].…”
Section: Discussionsupporting
confidence: 86%
“…Williams [7] and Roberts and Hamann [8] have reconstructed the evolution of land covered by several tree species in North America since the LGM, thereby allowing the identification of potential refugia for those species. Also, molecular studies have shown evidence of genetic structure for several North American plant species [914]. …”
Section: Introductionmentioning
confidence: 99%
“…However, more recent work by Anderson et al (2006Anderson et al ( , 2011 report phylogeographic evidence of possible local Beringian spruce populations, which reintroduces the notion of a glacial refugium. Brubaker et al (2005) suggest that spruce pollen values during the LGM and Lateglacial, while low, may nevertheless indicate restricted spruce populations.…”
Section: Spruce and Early-holocene Treeline In Northwest Alaskamentioning
confidence: 96%
“…For many widespread tree species, it is precisely the populations at the edge of the distribution range that accumulate most of the intraspecific genetic variation, either because they correspond to glacial (micro-) refugia (for example, Kelly et al, 2010;Anderson et al, 2011), or because they represent contact zones between migrants from such refugia (Hewitt, 2004;Magri et al, 2006). Conservation of natural marginal populations of species has therefore long been considered crucial for the preservation of genetic diversity and evolutionary potential (Newton et al, 1999;Moritz, 2002).…”
Section: Introductionmentioning
confidence: 99%